2013
DOI: 10.1037/a0030318
|View full text |Cite
|
Sign up to set email alerts
|

Head start early mental health intervention: Effects of child-centered play therapy on disruptive behaviors.

Abstract: This pilot study examined the effectiveness of child-centered play therapy (CCPT) with 54 low income preschool children (42% African American, 39% Hispanic, and 18% Caucasian) identified with clinical levels of disruptive behaviors. Children were assigned to the experimental treatment, CCPT, or to the active control, reading mentoring (RM), through block randomization. Results from a 2 (group) × 3 (measures) split plot analysis of variance indicated that according to teachers blinded to children's treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 51 publications
8
71
0
2
Order By: Relevance
“…Similarly, the results of the study by Baggerly (2004) showed that child-centered play therapy increases children's selfesteem. In addition, the results of this research are in line with studies that indicate play therapy to be influential in reducing the behavioral problems among children [20,21,33] and studies that show group play therapy improves children's social skills [15], as well as with studies revealing play therapy to increase children's self-esteem [16].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, the results of the study by Baggerly (2004) showed that child-centered play therapy increases children's selfesteem. In addition, the results of this research are in line with studies that indicate play therapy to be influential in reducing the behavioral problems among children [20,21,33] and studies that show group play therapy improves children's social skills [15], as well as with studies revealing play therapy to increase children's self-esteem [16].…”
Section: Discussionsupporting
confidence: 74%
“…Since a systematic literature review revealed that there have been no studies conducted that focused on the role of CBPT in enhancing self-esteem in children with intellectual disability [11,19], though it seems that attention to this issue may prevent incidence of more serious problems such as deviant behaviors [20], psychosomatic disorders [21] and depression with suicidal thinking [22] in such children in adulthood; this study aimed to evaluate the effectiveness of CBPT on self-esteem of children with intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…With limit setting, a child presenting externalizing behavioral concerns experiences different approaches to expressing feelings and behaviors that result in decreases in the child's oppositional behaviors (Trice-Black et al, 2013). The effectiveness of CCPT with externalizing behaviors has also been reported by previous researchers (Bratton et al, 2013;Cochran et al, 2011;Cochran, Cochran, Fuss, & Nordling, 2010;Ray et al, 2009;Schumann, 2010).…”
Section: How Ccpt Play Therapy Work For Children Exhibiting Internalmentioning
confidence: 67%
“…During the past few years, play therapy researchers have responded to the need for more rigorous empirical evidence to advance play therapy to higher placement in EBT criteria categories. One example is an RCT designed to examine child-centered play therapy (CCPT) for preschool children with clinical levels of disruptive behaviors (Bratton et al, 2013). This RCT met all five methods criteria outlined by Southam-Gerow and Prinstein (2014).…”
Section: Play Therapy Research In the 21st Century And Individual Stumentioning
confidence: 99%
“…One experiment has met all five methods criteria, but it cannot be considered a level 1 treatment until another study of equal methodological caliber is conducted by a different research team. Another recent treatment study, conducted by some of the same authors and using almost identical study design as Bratton et al (2013), provided evidence for Adlerian play therapy as another level 2 treatment for disruptive behavior (Meany-Walen, Bratton, & Kottman, 2014). While the remainder of play therapy interventions published since the year 2000 remain at level 4, there has been a growing number of 21st-century experimental and quasi-experimental research studies indicating positive treatment effects for several presenting problems, including internalizing problems (Packman & Bratton, 2003), ADHD (Ray, Schottelkorb, & Tsai, 2007), trauma (Schottelkorb, Doumas, & Garcia, 2012;Tyndall-Lind, Landreth, & Giordano, 2001;Shen, 2002), academic problems (Blanco & Ray, 2011), delayed language skills (Danger & Landreth, 2005), teacher-child relationship problems (Ray, 2007;Ray, Henson, Schottelkorb, Brown, & Muro, 2008), and adaptation to medical problems (Bloch & Toker, 2008;Jones & Landreth, 2002;Li & Lopez, 2007;Tsai et al, 2013).…”
Section: Play Therapy Research In the 21st Century And Individual Stumentioning
confidence: 99%